2022
DOI: 10.1186/s12883-022-02845-5
|View full text |Cite
|
Sign up to set email alerts
|

Baseline platelet count may predict short-term functional outcome of cerebral infarction

Abstract: Background and aims Platelets play an important role in homeostasis however, they have also been associated with increased mortality after myocardial infarction. In the present study, we investigated whether platelet count is associated with differences in the short-term prognosis at the time of hospital discharge and early neurological deterioration in ischemic stroke patients. Methods Patients with ischemic stroke were enrolled from among 661 cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
0
2
Order By: Relevance
“…However, Guo et al [23] and Jo et al [24] published an article and our study did not find a significant correlation between WBC count and MCE, which could be attributed to the differences in the populations included in the study. Many previous studies on MCE have not included PLT as a variable, and conclusions regarding PLT count and the prognosis of cerebral infarction have also been inconsistent [27,43,49,50]. However, our study found that a reduced PLT count was a risk factor for MCE.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, Guo et al [23] and Jo et al [24] published an article and our study did not find a significant correlation between WBC count and MCE, which could be attributed to the differences in the populations included in the study. Many previous studies on MCE have not included PLT as a variable, and conclusions regarding PLT count and the prognosis of cerebral infarction have also been inconsistent [27,43,49,50]. However, our study found that a reduced PLT count was a risk factor for MCE.…”
Section: Discussioncontrasting
confidence: 68%
“…Many previous studies on MCE have not included PLT as a variable, and conclusions regarding PLT count and the prognosis of cerebral infarction have also been inconsistent [27, 43, 49, 50]. However, our study found that a reduced PLT count was a risk factor for MCE.…”
Section: Discussioncontrasting
confidence: 59%